Roles of SPI-2 T3SS effectors in virulence of Salmonella Choleraesuis and Construction of a triple-gene mutant vaccine strain - Xu, Rui; Ji, Xiangfei; Lian, Junqi; Zhu, Dekang; Liu, Mafeng; Wang, Mingshu; Jia, Renyong; Chen, Shun; Yang, Qiao; Wu, Ying; Zhang, Shaqiu; Huang, Juan; et al. (Frontiers in Veterinary Science, 2025)
Effector protein functions of Type III secretion system (T3SS) encoded by Salmonella pathogenicity islands 2 (SPI-2) have not been fully characterized in Salmonella enterica serovar Choleraesuis. This study characterized 21 effectors of SPI-2 T3SS of S. Choleraesuis in terms of macrophage survival and virulence in mice via construction of various gene mutant strains. Eight effector genes including sseF, sseJ, sifB, sseK, sifA, sopD2, steC, and steD contributed to bacterial survival in macrophage cell line RAW264.7; whereas only sopD2 also promoted bacterial virulence in mice like other three effector genes sseL, steA, and spiC. The mutant strain, ΔsopD2, ΔsseL, ΔsteA, or ΔspiC, led to higher mouse survival compared to the wild-type strain post-oral infection, while their bacterial loads in spleen and liver were not reduced except the ΔspiC that was undetectable in mouse tissues. Then, the triple-gene mutant strain ΔsseLΔsopD2ΔsteA was constructed and found to be virulence attenuated with a compromised colonization ability. Finally, immunization of this mutant orally induced robust serum IgG responses and provided 40% protection against lethal S. Choleraesuis challenge. Our study highlights the critical role of four SPI-2 T3SS effectors in S. Choleraesuis pathogenesis.